2022
DOI: 10.3390/ijerph19031202
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Physiological and Psychological Effects of Digital Shinrin-Yoku and Its Characteristics as a Restorative Environment

Abstract: This study investigated the physiological and psychological therapeutic effects of a digital Shinrin-yoku environment constructed indoors in an urban facility as well as the characteristics of the environment that contribute to restorativeness (restorative traits). We measured the fluctuations in the physical and mental states of 25 subjects by obtaining both before–after measurements and continuous measurements while exposed to a digital Shinrin-yoku environment that reproduced visual, auditory, and olfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…Among the four studies utilizing virtual nature-based interventions, three were rated as good quality [35 ▪▪ ,36 ▪▪ ,37] while one received a fair rating [38 ▪ ]. All studies reported a significant reduction in anxiety and depression following the digital intervention or some arrangement thereof (e.g., a specific order for presenting digital stimuli).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the four studies utilizing virtual nature-based interventions, three were rated as good quality [35 ▪▪ ,36 ▪▪ ,37] while one received a fair rating [38 ▪ ]. All studies reported a significant reduction in anxiety and depression following the digital intervention or some arrangement thereof (e.g., a specific order for presenting digital stimuli).…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported a significant reduction in anxiety and depression following the digital intervention or some arrangement thereof (e.g., a specific order for presenting digital stimuli). Notably, the study conducted in Japan [37] adhered to a rigorous design. Despite involving only 25 participants in a 20-min digital forest bathing session, the stimuli encompassed visual, audible, and olfactory domains, providing participants with a more realistic experience of a natural environment.…”
Section: Resultsmentioning
confidence: 99%
“…This would ease the mind, dispel fatigue, relieve stress, and cultivate a healthy complexion (9). Relevant studies in Germany have demonstrated that the natural environment can contribute to releasing stress, and Germany has taken the lead in establishing the first forest recreation sites in the world (10)(11)(12)(13). At present, the concept of a healing environment is a more comprehensive generalization and summary of "forest bath" and "natural therapy", which makes the understanding of the medicalization of natural environmental resources more diverse and profound (12,13).…”
Section: Original Articlementioning
confidence: 99%
“…Relevant studies in Germany have demonstrated that the natural environment can contribute to releasing stress, and Germany has taken the lead in establishing the first forest recreation sites in the world ( 10 - 13 ). At present, the concept of a healing environment is a more comprehensive generalization and summary of “forest bath” and “natural therapy”, which makes the understanding of the medicalization of natural environmental resources more diverse and profound ( 12 , 13 ). Based on Germany’s experience, Japan has developed various alternative therapies based on forest resources, including horticultural therapy, wilderness healing and climatic terrain therapy, and other “nature-based medicine” approaches.…”
Section: Introductionunclassified
“…It has been demonstrated that watching pictures of real nature will improve human health [ 17 ], reduce stress, improve mood [ 18 ], relieve fatigue [ 19 ], and improve cognition [ 20 ]. Exposure to virtual nature also has restorative traits similar to exposure to real nature [ 21 ]. Watching virtual reality (VR) natural scenery can reduce stress [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%